PENGARUH ACTIVE ASSISTIVE RANGE OF MOTION TERHADAP KADAR GULA DARAH 2 JAM POSTPRADIAL PADA PASIEN DENGAN DIABETES MELITUS TIPE II - Made Someita (Coping: Community of Publishing in Nursing, 2015)
Diabetes Mellitus Type II is a group of metabolic diseases, which has a characteristic such as high blood glucose level. Physical exercises are one of recommended therapies to reduce blood glucose level for the people with diabetes mellitus type II. AAROM is one of physical exercise like isotonic movement. AAROM increase the requirement of energy, the absorbsion of glucose by muscle, and could increase the metabolism of our body. This study aim to find the effect of AAROM on 2 hour postpradial blood sugar toward the patient who has diabetes mellitus type II. This study is the Quasi-Experimental that used Non-Equivalent control group design. This study was conducted on 26 respondents by using a purposive sampling technique. AAROM was given to treatment group twice on each day for 4 days with the duration ±20 minutes. The data analysis is used in this study, consists of Parametric test that is Paired t-Test and Independent t-Test with the reability 95% (?=0.05). The result of the analysis using paired t-Test showed that there is a difference between blood glucose levels in the Pre Test and Post Test toward the treatment group and control group (p value = 0.000) with the decrease of 2 hour postpradial blood glucose in treated group 93.154 and 69.462 in control group. The analysis of independent t-Test shows that there is the difference effect of AAROM on 2 hour postpradial in treated group and control group (p value = 0.023). Therefore, it can be concluded that there is an effect of AAROM on 2 hour postpradial blood glucose level toward diabetes mellitus’s patient type II. Based on the finding of the study, it is suggested to nurse for using AAROM as the one of physical exercise therapy towards DM type II patient who is being hospitalized